What the pediatric endocrinologist needs to know about skeletal dysplasia, a primer - Legare, Janet M.; Basel, Donald (Frontiers in Pediatrics, 2023)
Children with skeletal dysplasia are frequently referred to pediatric endocrinologists due to short stature. These children may present with disproportionate growth or medical histories that point to a skeletal dysplasia. This primer will discuss when to be concerned about skeletal dysplasia, the initial steps in evaluation for a skeletal dysplasia, and new therapies that are either recently approved or in development.